Umbilical Hernia Repair: Analysis after 934 Procedures. Issue 9 (September 2015) - Porrero, Jose L.; Cano-Valderrama, Oscar; Marcos, Alberto; Bonachia, Oscar; Ramos, Beatriz; Alcaide, Benito; Villar, Sol; SÁNchez-Cabezudo, Carlos; QuirÓS, Esther; Alonso, María T.; Castillo, María J.
There is a lack of consensus about the surgical management of umbilical hernias. The aim of this study is to analyze the medium-term results of 934 umbilical hernia repairs. In this study, 934 patients with an umbilical hernia underwent surgery between 2004 and 2010, 599 (64.1%) of which were evaluated at least one year after the surgery. Complications, recurrence, and the reoperation rate were analyzed. Complications were observed in 5.7 per cent of the patients. With a mean follow-up time of 35.5 months, recurrence and reoperation rates were 3.8 per cent and 4.7 per cent, respectively. A higher percentage of female patients (60.9 % vs 29 %, P = 0.001) and a longer follow-up time (47.4 vs 35 months, P = 0.037) were observed in patients who developed a recurrence. No significant differences were observed between complications and the reoperation rate in patients who underwent Ventralex® preperitoneal mesh reinforcement and suture repair; however, a trend toward a higher recurrence rate was observed in patients with suture repair (6.5 % vs 3.2 %, P = 0.082). Suture repair had lower recurrence and reoperation rates in patients with umbilical hernias less than 1 cm. Suture repair is an appropriate procedure for small umbilical hernias; however, for larger umbilical hernias, mesh reinforcement should be considered.